The Atg1 Kinase Complex Is Involved in the Regulation of Protein Recruitment to Initiate Sequestering Vesicle Formation for Nonspecific Autophagy in Saccharomyces cerevisiae - Cheong, Heesun (The American Society for Cell Biology, 2008)
Autophagy is the major degradative process for recycling cytoplasmic constituents and eliminating unnecessary organelles in eukaryotic cells. Most autophagy-related (Atg) proteins are recruited to the phagophore assembly site (PAS), a proposed site for vesicle formation during either nonspecific or specific types of autophagy. Therefore, appropriate recruitment of Atg proteins to this site is critical for their function in autophagy. Atg11 facilitates PAS recruitment for the cytoplasm-to-vacuole targeting pathway, which is a specific, autophagy-like process that occurs under vegetative conditions. In contrast, it is not known how Atg proteins are recruited to the PAS, nor which components are involved in PAS formation under nonspecific autophagy-inducing, starvation conditions. Here, we studied PAS assembly during nonspecific autophagy, using an atg11Δ mutant background to eliminate the PAS formation that occurs during vegetative growth. We found that protein complexes containing the Atg1 kinase have two roles for PAS formation during nonspecific autophagy. The Atg1 C terminus mediates an interaction with Atg13 and Atg17, facilitating a structural role of Atg1 that is needed to efficiently organize an initial step of PAS assembly, whereas Atg1 kinase activity affects the dynamics of protein movement at the PAS involved in Atg protein cycling.